Clinical controversies: Proton radiation therapy for brain and skull base tumors - Combs, Stephanie E.; Laperriere, Normand; Brada, Michael (Seminars in Radiation Oncology, 2013)
Proton radiotherapy offers distinct physical properties that could lead to an improvement of dose distribution with subsequent reduction of integral dose to the patient. This supports the potential use of proton beams in tumors close to sensitive structures, such as the skull base and the brain. In the present manuscript, the literature on proton therapy for brain and skull base tumors is critically reviewed and compared with results obtained with modern photon techniques. Treatment planning comparisons demonstrate that dose distributions within the target are comparable. In terms of normal tissue dose distribution, protons offer an advantage in the intermediate- and low-dose regions, and this may result in long-term clinical benefit, although to date no randomized or long-term follow-up data demonstrate this. Considering the excellent long-term results seen with photons in localized tumors, this benefit may be modest and difficult to demonstrate. Protons may allow for safe delivery of higher local doses with the potential to improve local control in some tumors. However, improvements in photon techniques also enable safe dose escalation, and therefore, the comparison of the techniques of delivery is likely to need randomized trials. Proton therapy offers effective treatment for a range of brain tumors. However, the limited availability, the cost, and the lack of evidence of superiority mean that advanced photon radiotherapy continues to be the treatment of choice. It is hoped that advances in technology, both in proton and photon radiotherapy delivery, and increasing information on the efficacy and toxicity of the two modalities will lead to further improvement in radiotherapy approaches and provide the basis for the best choice of treatment for the individual patient. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-08